Going global: The role of gatekeepers in the transnational reception of defne suman’s the silence of scheherazade - DOĞANGÜN, SİMLA AYŞE (My University, 2022)
Going Global: The Role of Gatekeepers in the Transnational Reception of Defne Suman’s The Silence of ScheherazadeOn August 12, 2021, with hashtags, #historicalfiction, #translatedfiction, #greece, #turkey, #armenia, #levant #empire, #Scheherazade, Defne Suman announced the release of her English-language debut novel, The Silence of Scheherazade on social media. The novel centres on the tale of the burning of Smyrna in 1922, told through Levantine, Greek, Turkish and Armenian inhabitants of the city. Her gatekeepers, Head of Zeus Independent Publishing Company, the book’s translator Betsy Göksel and her literary agent Nermin Mollaoğlu were among the first ones to receive tribute for their hard work and support in the process. In the following months, Maureen Freely hosted the book’s launch in an online event, organized by Powell’s Books in Portland, Oregon. Succeeding interviews, book reading events and podcasts concentrated on the writer’s upbringing, other authors who influenced the style of the author, the translation process, the role of history in the book, as well as the motivation behind its title, which was different from its Turkish version, Emanet Zaman (2016).If World Literature is constituted by \"literary works that circulate beyond their culture of origin, either in translation or in their original language,\" as Damrosch (2003: 4) states, then, other actors who are involved in the work’s interaction with the world audience pave the way for its success in the global market, as William Marling claims in Gatekeepers: The Emergence of World Literature in the 1960s (2016:1). Taking its cue from the convergence of these insights, the paper focuses on the multi-layered gatekeeping process of Suman’s Scheherazade and explores the ways in which people and institutions have become integral components of its global dissemination.Works CitedDamrosch, David (2003) What is World Literature? Princeton and Oxford: Princeton University Press.Marling, William (2016) Gatekeepers: The Emergence of World Literature and the 1960s. New York: Oxford University Press.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; Social Sciences and Humanities; Philology; Western Languages and Literatures; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; EDEBİYAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; LITERATURE; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities